Epicardial Adipose Tissue: Another Tassel in the Complex Fabric of Atherosclerosis - Alexopoulos, Nikolaos; Raggi, Paolo (Cardiovascular & Haematological Disorders - Drug Targets, 2018)
Atherosclerosis affects the majority of adult individuals in industrialized nations and it is beginning to affect even traditionally spared populations. The classic view has been that the precipitating events are intraluminal. However, good evidence supports the possibility that at least part of the atherosclerosis burden may be the consequence of extra-luminal noxious stimuli. Additionally, the epidemic of obesity, insulin resistance and diabetes mellitus has generated a strong interest in the potential role of visceral adipose tissue as an extra-luminal promoter of atherosclerosis. The epicardial space is filled with adipose tissue with an embryological origin similar to that of abdominal visceral fat. Both fats are highly inflamed in obese patients, patients with the metabolic syndrome and in those with established coronary artery disease. Additionally they are capable of secreting large quantities of pro-inflammatory cytokines and free fatty acids but also anti-inflammatory adipokines like adiponectin. In this manuscript we review the current evidence supporting the role of epicardial adipose tissue in the development of atherosclerosis and its complications.
Keywords: insulin